Why do ventilation strategies matter in controlling infectious airborne particles? A comprehensive numerical analysis in isolation ward. (1st March 2023) - Tan, Huiyi; Wong, Keng Yinn; Othman, Mohd Hafiz Dzarfan; Kek, Hong Yee; Nyakuma, Bemgba Bevan; Ho, Wai Shin; Hashim, Haslenda; Wahab, Roswanira Abdul; Sheng, Desmond Daniel Chin Vui; Wahab, Nur Haliza Abdul; Yatim, Ardiyansyah Saad
Abstract: A proper ventilation strategy in an isolation ward could promote better indoor air quality for the occupants. This could also reduce the risk of immunocompromised patients contracting healthcare-associated infections (HAI) or airborne diseases such as COVID-19, tuberculosis, and measles among others. This study aims to propose and examine appropriate ventilation strategies in a single-patient isolation ward that can reduce particle settlement in patients. A simplified CFD model of the isolation ward was developed and well-validated against established data. An RNG k-ε model and discrete phase model (DPM) were used to simulate airflow and particle transportation. The study examined the airflow and particle dispersion under a baseline case and four proposed ventilation strategies. Results showed that the baseline case study, which used the ceiling-mounted air curtain was insufficient to prevent the particles from dispersing into the vicinity of the patient. Likewise, the dilution effect under the baseline case and case 4 (wall-mounted air supply diffuser) were relatively weak due to the low air change rate (ACH) of 4/hr and 9/hr respectively. The ventilation strategy in case 4 has a negligible effect on reducing the particles (14%) settling on the patient although the ACH in case 4 was 2-times the baseline case. The present finding ascertains that utilising the combination of ceiling-mounted air diffuser and air curtain jet (case 3) results in zero particle settlement on both patient's and the patient's bed. It also reduced 57% of particles in the vicinity of the medical staff's breathing zone compared to the baseline case. Highlights: Ceiling-mounted air curtain was insufficient to prevent the particles from dispersing into the vicinity of the patient. The dilution effect under the ceiling-mounted air curtain and wall-mounted air supply diffuser were relatively weak. Utilising the combination of ceiling-mounted air diffuser and air curtain jet results in zero particle settlement.